Scientific contemporary in al-Quran interpretation: An review for al-Sha'rawi method in Tafsir al-Sha'rawi - Amir, S. (2017)
Syeikh Muhammad Mutawalli al-Sha‘rawi is a renown Egypt nativity scholar for his knowledge credibility in numerous fields. His activeness in the field of da’wah and social has leaped him as a renowned contemporary da’ie murabbi. His approach concerning the current philosophical interpretation in al-Quran comprehension is a noble effort in integrating ma’na and isyarah comprised in al-Quran which is in line with the current scientific. Currently he gives new aspiration upon community reformation towards the authentic Islamic teaching as Muslim community is enchained with the culture as well as knowledge secularism and liberalism. The summit of al-Sha’rawi battle on ennobling Islamic law is visible via his masterpiece entitled Tafsir al-Sha‘rawi. Early analysis shows that he applied approach of al-‘Ilmi al-Naqli al-Ijtima‘ie methodology in interpreting al-Quran by using combination of numerous scientific elements such as divine science, social science and natural science in which were already comprised in his tafsir. Thus, it is justified to be highlighted to the community so that his knowledge would be able to exist in terms of future framework for current knowledge urbanization besides unveiling current scientific of al-Quran prospect. Hence, this article will pursue al-Sya’rawi’s scientific method that has been applied in his tafsir.